Extraction of parabens from cosmetic and environmental water samples coupled with uv-visible spectroscopy - Beh, S. Y.; D. Mahfut, I. W. B.; M. Juber, N. I. B.; Asman, S.; Yusoff, F.; N. M., Saleha (2021)
An effective and fast vortex-assisted dispersive liquid–liquid extraction method was developed for the extraction of paraben in cosmetic samples and water samples. The paraben was determined and quantifi ed using ultraviolet-visible (UV-Vis) spectrometry. A response surface methodology (RSM) based on the central composite design was used for the optimization of factors (composition of the extractant, volume of extractant, extraction time, centrifugation time, and centrifugation velocity) affecting the extraction effi ciency of the procedure. The optimum parameters for vortexassisted dispersive liquid–liquid extraction (VA-DLLE) are: chloroform used as the extractant solvent, 5 ml volume of extractant, 3 min extraction time, 5 min centrifugation time, and 2400 rpm centrifugation velocity. The limit of detection (LOD) and the limit of quantifi cation (LOQ) for paraben are 0.0476 and 0.1442 μg/mL, respectively. Spiked cosmetic samples have the extraction recoveries in the range of 81.2–96.8%, whereas spiked water sample extraction recoveries were in the range of 88.8–100.63%. Each sample was repeated (n = 2), with a relative standard deviation of <5.74% for cosmetic samples and <9.03% for water samples. In conclusion, this extraction method is fast and inexpensive for the extraction of paraben.